Neglected zygomaticomaxillary complex fracture: Report of two cases during the COVID-19 pandemic - Ananda, Nissia; Ariawan, Dwi; Julia, Vera (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: The COVID-19 pandemic spread rapidly worldwide, including in Indonesia. As a result, people developed a fear of visiting hospitals and a tendency to ignore symptoms unrelated to COVID-19. A zygomaticomaxillary complex bone fracture is one of the most frequent midface fractures and is often accompanied by infraorbital nerve paresthesia. Purpose: This article aims to report two cases of neglected zygomaticomaxillary complex bone fractures with persistent infraorbital nerve paresthesia caused by the patient’s fear of seeking medical care. Cases: The first case is a 19-year-old male with a history of trauma two weeks prior to hospital admission. He was diagnosed with a neglected zygomaticomaxillary complex bone fracture, which resulted in persistent infraorbital nerve paresthesia. This condition was due to the patient’s fear of visiting the hospital. The second case is a 21-year-old female who presented with a history of persistent numbness on the left cheek and upper lip for one month prior to hospital admission. The symptoms originated from an accident where the patient fell from a ladder measuring two meters in height. Case management: Surgical intervention—open reduction and internal fixation (ORIF)—was performed on both patients to promote nerve recovery. However, there is ongoing debate regarding the safety of elective oral maxillofacial surgery procedures during the COVID-19 pandemic. After a follow-up period, both patients experienced a recovery of sensory function in the infraorbital nerve. Conclusion: Infraorbital nerve sensory disturbance along with zygomaticomaxillary complex bone fracture found during the COVID-19 pandemic should be managed with ORIF to improve nerve recovery.